2013
DOI: 10.1080/00207160.2013.770483
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of the needle eccentricity on the internal flow in diesel injector nozzles by computational fluid dynamics calculations

Abstract: (October 2012) In the present paper, a computational study has been performed in order to clarify the effects of the needle eccentricity in a real multihole microsac nozzle. This nozzle has been simulated at typical operating conditions of a diesel engine, paying special attention to the internal flow development and cavitation appearance within the discharge orifices. For that purpose, a multiphase flow solver based on a homogeneous equilibrium model with a barotropic equation of state has been used, intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A uniform pressure boundary with a turbulent intensity of 4.4% is applied over the sac entry plane. Thus, any effects due to turbulence or flow asymmetry generated in the passage between the needle and seat [60][61][62][63][64] air. This initial stage is somewhat arbitrary and the rationale is described in Ghiji et al [65].…”
Section: Boundary Conditions and Initial Set-upmentioning
confidence: 99%
“…A uniform pressure boundary with a turbulent intensity of 4.4% is applied over the sac entry plane. Thus, any effects due to turbulence or flow asymmetry generated in the passage between the needle and seat [60][61][62][63][64] air. This initial stage is somewhat arbitrary and the rationale is described in Ghiji et al [65].…”
Section: Boundary Conditions and Initial Set-upmentioning
confidence: 99%
“…This phenomenon was also detected computationally by means of a simulation of the flow with a Volume Of Fluid (VOF) model implemented in STAR-CD. The effects of needle eccentricity were also studied computationally with OpenFOAM by Salvador et al, 29 who observed important hole-to-hole differences in the internal flow and strong variations in the cavitation generated among the orifices. Salvador et al showed that an eccentric position of the needle produces lower values for mass flow, momentum flux and effective velocity at the nozzle exit.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies focus on the effects of the injector geometry on the injection system performance [15]- [17]. On the one hand, the dimensions of the injector internal passages, including the control volume orifices, are critical for the injector needle dynamics and consequently the opening and closing slopes of the injection rate profile [18]- [20]. These effects are particularly important when using multiple injection strategies, since the injector acoustics also affect the needle motion [21], [22].…”
Section: Introductionmentioning
confidence: 99%